The impact of COVID-19 on psychiatric and mental health services in Europe: suffering experienced by professionals - Hélène Kane; Jade Gourret Baumgart; Emmanuel Rusch; Jocelyn Deloyer; Claudio Fuenzalida; Gabriela Kelemen; Marek Krzystanek; Donatella Marazziti; Margarita Moraitou; Merja Reunanen; Rexhaj Shyhrete; Johannes Thome; et al. (BMC, 2022)
Abstract Background The COVID-19 pandemic has not only impacted intensive care units, but all healthcare services generally. This PsyGipo2C project specifically investigates how psychiatry and mental health professionals have been affected by the reorganizations and constraints imposed, which have reshaped their often already difficult working conditions. Methods Our research combined quantitative and qualitative methods, surveying and interviewing health professionals of all occupations working in psychiatric and mental health services. A questionnaire was completed by 1241 professionals from 10 European countries, and 13 group interviews were conducted across 5 countries. In addition to this, 31 individual interviews were conducted in Belgium and France. Results Among the questionnaire respondents, 70.2% felt that their workload had increased, particularly due to their tasks being diversified and due to increased complexity in the provision of care. 48.9% felt that finding a work-life balance had become more difficult, and 59.5% felt their health had been affected by the crisis. The impact of the health crisis nevertheless varied across professions: our data provides insight into how the health measures have had a differential impact on professional tasks and roles across the various categories of occupations, obliging professionals to make various adaptations. The distress incurred has been linked not only to these new constraints in their work, but also to the combination of these with other pressures in their personal lives, which has consequently compromised their well-being and their ability to cope with multiple demands. Discussion The COVID-19 health crisis has had varying impacts depending on the profession and access to remote work, sometimes leading to conflicts within the teams. The suffering expressed by the professionals was tied to their values and patterns of investment in work. Our research also highlights how these professionals made little use of the psychological supports offered, probably due to a reluctance to acknowledge that their mental health was affected.